2016
DOI: 10.3390/s16020218
|View full text |Cite
|
Sign up to set email alerts
|

Spray Droplet Characterization from a Single Nozzle by High Speed Image Analysis Using an In-Focus Droplet Criterion

Abstract: Accurate spray characterization helps to better understand the pesticide spray application process. The goal of this research was to present the proof of principle of a droplet size and velocity measuring technique for different types of hydraulic spray nozzles using a high speed backlight image acquisition and analysis system. As only part of the drops of an agricultural spray can be in focus at any given moment, an in-focus criterion based on the gray level gradient was proposed to decide whether a given dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…A conclusion of the previous works showed an effect of variability of working pressure in the Dv 0.5 at a constant nozzle type (Alheidary, (2); Alheidary, (3). The results of this point are agreed with the results of (15,17,18,23) which confirmed effect of the droplet sizes by changing in working pressure. All tests investigated decrease of the droplet size with target distance download increase.…”
Section: Results and Discussion Effect Of Nozzle Type Working Pressusupporting
confidence: 90%
“…A conclusion of the previous works showed an effect of variability of working pressure in the Dv 0.5 at a constant nozzle type (Alheidary, (2); Alheidary, (3). The results of this point are agreed with the results of (15,17,18,23) which confirmed effect of the droplet sizes by changing in working pressure. All tests investigated decrease of the droplet size with target distance download increase.…”
Section: Results and Discussion Effect Of Nozzle Type Working Pressusupporting
confidence: 90%
“…More importantly, data analysis in both LD and PDPA is based on the assumption of spherical droplets, which is never strictly satisfied for a spray process and becomes problematic with increasing droplet size. Imaging-based techniques can overcome all the above limitations by providing high resolution size measurements on a per-drop basis over a large field-of-view from the captured images (Jiang et al, 2010;Minov et al, 2016). However, conventional imaging techniques have limited depth of field, i.e., the depth that the object appears to be in focus, which decreases drastically with increasing magnification.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, the smallest spray droplets can impact WPCs (Minov et al, 2016;Alheidary, 2019). The results also showed that these properties were significantly affected by the positions of WPCs on the plant.…”
Section: Table (5): the Average And Sd Values Of The Spray Droplet Properties At Different Positions Of The Plant Based On Nozzle Typementioning
confidence: 80%